2014
DOI: 10.2166/ws.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of groundwater fluorine levels and other characteristics in two areas of Laizhou Bay and its explanation on fluorine enrichment

Abstract: The groundwater characteristics in two areas, Tushan town (TS) in Laizhou County and Puzhuang town (PZ) in Changyi County, were compared to discuss the dynamics of fluorine enrichment. Groundwater has average fluorine levels of 2.33 mg/L in PZ town ranging from 0.65 to 9.87 mg/L and of 0.91 mg/L ranging from 0.27 to 1.25 mg/L in TS town. The geochemical indexes indicate seawater intrusion in the both areas, the more serious seawater intrusion in PZ town causes the higher pH, electrical conductivity (EC), total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The China Geological Survey has set the seawater intrusion standards by Cl À of 250 mg/L, Br À of 0.55 mg/L, and TDS of 1.0 mg/L (Wang et al 2015). The supplied water was characterized by non-intrusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The China Geological Survey has set the seawater intrusion standards by Cl À of 250 mg/L, Br À of 0.55 mg/L, and TDS of 1.0 mg/L (Wang et al 2015). The supplied water was characterized by non-intrusion.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the NaF solubility is remarkably higher than CaF 2 or MgF 2 (Chae et al 2007;Chen et al 2012Chen et al , 2019Chen et al , 2020b. Meanwhile, the fluoride levels in groundwater are restricted by Ca 2þ levels because of the low CaF 2 solubility, and Ca 2þ -F À negative relationship in groundwater is commonly observed and documented (Ozsvath 2009;Wang et al 2015). The leached fluoride from rock (soil) and groundwater fluoride levels are also proved to increase with Na þ increasing and Ca 2þ decreasing by field investigations or simulation experiments (Krainov & Zakutin 1994;Gao et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Na + –Ca 2+ cation exchange is the prominent process of sea water intrusion, including direct cation exchange (the groundwater Ca 2+ exchanges with the Na + in aquifer materials) and reverse cation exchange (the groundwater Na + exchanges with the Ca 2+ in aquifer materials). However, the reverse cation exchange was confirmed to occur at the initial stage of intrusion (Wu et al 1994; Wang et al 2015). Moreover, field investigation and simulation experiments in sea water intrusion areas also observed that Mg 2+ was less affected by cation exchange and that Na + –Mg 2+ exchange seldom occurs (Sajil Kumar et al 2014; Wang et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, the reverse cation exchange was confirmed to occur at the initial stage of intrusion (Wu et al 1994; Wang et al 2015). Moreover, field investigation and simulation experiments in sea water intrusion areas also observed that Mg 2+ was less affected by cation exchange and that Na + –Mg 2+ exchange seldom occurs (Sajil Kumar et al 2014; Wang et al 2015). Such different evolution processes of Ca 2+ and Mg 2+ can explain their different relationships with groundwater F − (Figure ).…”
Section: Resultsmentioning
confidence: 99%